Anle138b modulates α‐synuclein oligomerization and prevents motor decline and neurodegeneration in a mouse model of multiple system atrophy. Issue 2 (19th November 2018) - Heras‐Garvin, Antonio; Weckbecker, Daniel; Ryazanov, Sergey; Leonov, Andrei; Griesinger, Christian; Giese, Armin; Wenning, Gregor K.; Stefanova, Nadia
ABSTRACT: Background: MSA is a fatal neurodegenerative disease characterized by autonomic failure and severe motor impairment. Its main pathological hallmark is the accumulation of α‐synuclein in oligodendrocytes, leading to glial and neuronal dysfunction and neurodegeneration. These features are recapitulated in the PLP‐hαSyn mouse model expressing human α‐synuclein in oligodendrocytes. At present, there is no effective disease‐modifying therapy. Previous experiments have shown that the aggregation inhibitor, anle138b, reduces neurodegeneration and behavioral deficits in mouse models of other proteinopathies. Objectives: To test the therapeutic potential of anle138b in a mouse model of MSA. Methods: Two‐month‐old PLP‐hαSyn mice were fed over a period of 4 months with pellets containing anle138b at two different doses (0.6 and 2 g/kg) and compared to healthy controls and PLP‐hαSyn mice fed with placebo pellets. At the end of the treatment, behavioral and histological analyses were performed. Results: We observed a reversal of motor function to healthy control levels when PLP‐hαSyn mice were treated with both doses of anle138b. Histological and molecular analyses showed a significant reduction in α‐synuclein oligomers and glial cytoplasmic inclusions in animals fed with anle138b compared to nontreated mice. These animals also present preservation of dopaminergic neurons and reduction in microglial activation in SN correlating with the α‐synuclein reduction observed. Conclusions: Anle138b reduces α‐synuclein accumulation in PLP‐hαSyn mice, leading to neuroprotection, reduction of microglial activation, and preservation of motor function supporting the use of anle138b in a future clinical trial for MSA. © 2018 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.